Analysis Of Creative Thinking Abilities With The Implementation Of Problem-Based Learning Models Reviewed From The Fighting Power Of Junior High School Students - Siregar, Febry Azmiana; Sinaga, Bornok; Fauzi, Kms.M Amin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to: To analyze and the difficulty of the level of students' mathematical creative thinking ability after being given learning with the Problem-Based Learning model in terms of student fighting power; This type of research is Mix-Method Research. This research was conducted at Adhyaksa Medan Private Junior High School. The subjects in this study were class VIII-B students at Adhyaksa Medan Junior High School in the 2025/2026 Academic Year. Results of this study: Based on the results of the study, the level of students' mathematical creative thinking ability after being given learning with the problem-based learning model that out of 28 students there were 5 students (17.86%) who had very uncreative creative thinking ability, 10 students (35.71%) were less creative, 6 students (21.43%) were quite creative, 4 students (14.29%) were creative and 3 students (10.71%) were very creative. When viewed from their fighting power, there were 7 students in the quitter category consisting of 3 students with very creative abilities and 4 students who were less creative. In the Camper category, there are 12 students: 2 students with very low creative abilities, 6 students with less creative abilities, 2 students with moderate creative abilities, 1 student with creative abilities, and 1 student with very creative abilities. Meanwhile, the Climber category has 9 students, consisting of 4 students with moderate creative abilities, 3 students with creative abilities, and 2 students with very creative abilities